The changing structure of the maize seed industry in Zambia: Prospects for orange maize - Smale, Melinda; Simpungwe, Eliab; Birol, Ekin; De Groote, Hugo; Mutale, Raphael (International Food Policy Research Institute, 2013)
This paper reviews the changing structure of the maize seed industry in Zambia and presents findings of baseline and key informant interviews, in order to propose elements of a marketing strategy for the seeds of provitamin A-rich maize varieties. We discuss the merits of liberalizing germplasm provision to all seed companies vs those of exclusive rights to preserve product differentiation and ensure standard seed quality to protect the brand. We find that exclusive or not, risk-sharing arrangements with any company that takes up this product would be essential. Regardless of the involvement of the seed companies, building and maintaining a unique brand for provitamin A-rich maize that clearly distinguishes it from the many varieties that exist on the market will be fundamental to successful delivery strategies.